Influence Culture Organization on Practice Total Productive Maintenance (TPM) in Manufacturing Companies - Moch. Rizal (INSPIRETECH GLOBAL INSIGHT, 2026)
This study discusses the influence of organizational culture through the 8 pillars of TPM in improving the practice and implementation of Total Productive Maintenance (TPM) in manufacturing companies. Productive Maintenance (TPM) is A system or culture Which take ability and skills of each individual in an organization to carry out maintenance and upkeep on production equipment, this is an important strategy in manufacturing organizations in increasing their productivity. Literature study analysis was carried out on expert opinions and previous journals, research found that culture organization affect the whole pillar Total Productive Maintenance (TPM). The concept of Total Productive Maintenance (TPM) is a combination of organizational culture development and measurement practices, where an employee or production operator must have a good organizational culture so that they are able to develop the practices of Sorting Out, Arranging Efficiently, Checking Through Cleaning, Neatness, and Discipline.